Startup CEO a field guide to scaling up your business - Blumberg, Matt; Hindi, Hanny (Hoboken, New Jersey John Wiley & Sons, Inc., 2013)
A definitive book for any CEO first time or otherwise of a high-growth company While big company CEOs are usually groomed for the job for years, startup CEOs aren't and they're often young and relatively inexperienced in business in general.
Includes bibliographical references (pages 361-363) and index.
Keywords: New business enterprises -- Management; Corporate governance; Business and economics -- Industrial management